Middlemarch Epigraphs and Mirrors - Roberts, Adam (Open Book Publishers, 2021)
"In Middlemarch, George Eliot draws a character passionately absorbed by abstruse allusion and obscure epigraphs. Casaubon's obsession is a cautionary tale, but Adam Roberts nonetheless sees in him an invitation to take Eliot's use of epigraphy and allusion seriously, and this book is an attempt to do just that. Roberts considers the epigraph as a mirror that refracts the meaning of a text, and that thus carries important resonances for the way Eliot's novels generate their meanings. In this lively and provoking study, he tracks down those allusions and quotations that have hitherto gone unidentified by scholars, examining their relationship to the text in which they sit to unfurl a broader argument about the novel - both this novel, and the novel form itself. Middlemarch: Epigraphs and Mirrors is both a study of George Eliot and a meditation on the textuality of fiction. It is essential reading for specialists and students of George Eliot, the nineteenth century novel, and intertextuality. It will also richly reward anyone who has ever taken pleasure in Middlemarch."